Influence of Potassium Permanganate on Physicochemical Quality Attributes of Oil Palm (Elaeis guineensis Jacq.) Fresh Fruit Bunches - Imelya Ramanis; Deden Saprudin; Sudradjat Sudradjat (Jurnal Ilmu Pertanian Indonesia, 2026)
The physical and chemical properties of fresh fruit bunches (FFB) determine the quality of crude palm oil (CPO). The damage to the palm oil fruit accelerates the hydrolysis process, increasing the free fatty acid (FFA) content while decreasing the oil concentration. Damage is caused by the fruit's postharvest procedure, such as transportation time to the manufacturer and collection delays. The processing latency must be appropriate so that FFB damage can be reduced with potassium permanganate (KMnO4). The purpose of this study was to determine the effect of KMnO4 on the physical and chemical properties of palm oil FFB, as well as the relationship between the observed variables. The FFB samples were taken from the IPB-Cargill Palm Oil Teaching Farm in Jonggol Bogor, Indonesia. This study employed a randomized complete block design. The experiment included four different concentrations of KMnO4 (0%, 0,025%, 0,050%, and 0,075%). Each treatment was reproduced three times. The results showed that using KMnO4 could preserve the physical quality of palm oil fruit in terms of weight loss, fruit fall, respiration rate, and microbiological content. The chemical quality of fruit is determined by its moisture content and FFA concentration. The optimal KMnO4 concentration was 0.075%. The correlation analysis results show that the observed variables have a positive association. Variables with a strong relationship included weight loss and fruit fall, weight loss and several microbes, weight loss and number of microbes, water content and number of microbes, and FFA and number of bacteria. Keywords: crude palm oil, fresh fruit bunches, potassium permanganate, weight loss